The critical poem: Borges, Paz and other language-centered poets in Latin America. London, Cranbury : Associated University Press, 1996. - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filología y Literaturas Hispánicas, 1997)
Reseñado por Lucas Margarit
Fil: Margarit, Lucas. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina
Keywords: CRÌTICA; MILÁN, GONZALO; PAZ, OCTAVIO; DISCURSO POÉTICO; HUERTA, DAVID; BORGES, JORGE LUIS; GIRRI, ALBERTO; `PIZARNIK, ALEJANDRA; JUARROZ, ROBERTO; MARTÍNEZ, JUAN LUIS; RESEÑAS BIBLIOGRÁFICAS; POESÌA; RUNNING, THORPE